Creditworthiness and Reform in Poland Western and Polish Perspectives - Siwiński, Włodzimierz; Marer, Paul (Indiana University Press, 1988)
Many controversies surround Poland's economic and political future and the role that international financial institutions, Western governments and creditor banks should play in trying to shape it. The issues are discussed in this volume from a variety of perspectives, objectively and scientifically, with a minimum of jargon, and without pulling any punches.